The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1108/ijpsm-10-2015-0190
|View full text |Cite
|
Sign up to set email alerts
|

Co-production: what makes co-production work? Evidence from Pakistan

Abstract: 1 AbstractPurpose: In developing countries there is growing recognition that co-production offers more cost effective and responsive service delivery options in low income areas. This paper explores the way in which co-production initiatives are managed in a developing country, Pakistan.Design: A qualitative comparative case study design is used. Data is collected through 25 semi-structured interviews and document analysis and applies Institutional Analysis and Development (IAD) Framework for analysis. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…in co-production. Similar conclusions have been drawn from the studies of Alford (2016), Farooqi (2016, Fledderus (2015), Flemig and Osborne (2019), Lino et al (2019), Palumbo (2016), van Eijk and Steen (2016), and Verschuere et al (2012.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…in co-production. Similar conclusions have been drawn from the studies of Alford (2016), Farooqi (2016, Fledderus (2015), Flemig and Osborne (2019), Lino et al (2019), Palumbo (2016), van Eijk and Steen (2016), and Verschuere et al (2012.…”
Section: Discussionsupporting
confidence: 84%
“…First, similar to our research, the active engagement of users is indicated as vital for successful co-production by Dhirathiti (2018), Farooqi (2016), Lino et al (2019), andPoocharoen andTing (2015).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies highlight the importance of creating new structures within the organization to take responsibility for coproduction. New offices and positions can help create conditions that facilitate coproduction, such as increased accessibility, adaptability, and the improvement of coordination and shared decision making mechanisms (Farooqi, 2016;Farr, 2016;Sicilia et al, 2016;Tu, 2016;Workman, 2011). While the research is modest, some evidence suggests that the independence and agility of these offices may be important.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…14 In particular, co-production offers a valuable opportunity for vulnerable groups of actors to be heard. 11,15…”
Section: Introductionmentioning
confidence: 99%